FVA and electricity bill valuation adjustment - much of a difference? - Brigo,D; Fries,C; Hull,J; Scherer,M; Sommer,D; Werner,R (Springer, 2016)
Pricing counterparty credit risk, although being in the focus for almosta decade by now, is far from being resolved. It is highly controversial if any valuationadjustment besides the basic CVA should be taken into account, and ifso, for what purpose. Even today, the handling of CVA, DVA, FVA, ... differsbetween the regulatory, the accounting, and the economic point of view. Eventually,if an agreement is reached that CVA has to be taken into account, it remainsunclear if CVA can be modeled linearly, or if nonlinear models need tobe resorted to. Finally, industry practice and implementation differ in several aspects.Hence, a unified theory and treatment of FVA and alike is not yet tangible.The conference Challenges in Derivatives Markets, held at Technische Universitat¨Munchen in March/April 2015, featured a panel discussion with panelists repre- ¨senting different point of views: John Hull, who argues that FVA might not exist at all; in contrast to Christian Fries, who sees the need of all relevant costs to becovered within valuation but not within adjustments. Damiano Brigo emphasizesthe nonlinearity of (most) valuation adjustments and is concerned about overlappingadjustments and double-counting. Finally, Daniel Sommer puts the exit pricein the focus. The following (mildly edited) record of the panel discussion repeats themain arguments of the discussants – ultimately culminating in the awareness that ifeverybody charges an electricity bill valuation adjustment, it has to become part ofany quoted price.